The contentious politics of policy failure: The case of corporate board gender quotas in Spain. (April 2021) - Verge, Tània; Lombardo, Emanuela
Drawing on the insights of studies examining opposition to gender equality policy, this article develops an actor-centric analytical framework of the contentious politics underpinning the entire policy process and suggests that resistance is a crucial meta factor explaining policy failure. Through a longitudinal study of corporate board gender quotas in Spain, it investigates the ways in which enduring conflict between support and opposition actors can lead to policy failure at the different stages of the policy cycle. The article shows that resistance by status quo actors can undermine policy legitimacy and weaken its design at the adoption phase. Subsequently, resistance can lead not only to a poor implementation and evaluation work, resulting in policy incoherence, but also to the reinstatement of old assumptions. Ultimately, resistance may bring about the dilution of the policy's core ideas, the reduction of its scope and the dismantling of its governing arrangements, thereby hindering its durability. Our empirical analysis also reveals that policy failures can trigger actors' policy learning and yield interest realignments of advocacy coalitions aimed at reformulating the policy to enhance its effectiveness.